2019
DOI: 10.1098/rstb.2019.0212
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of past climate change and recent human persecution on mitogenomic diversity in the arctic fox

Abstract: Ancient DNA provides a powerful means to investigate the timing, rate and extent of population declines caused by extrinsic factors, such as past climate change and human activities. One species probably affected by both these factors is the arctic fox, which had a large distribution during the last glaciation that subsequently contracted at the start of the Holocene. More recently, the arctic fox population in Scandinavia went through a demographic bottleneck owing to human persecution. To investigate the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Nevertheless, to increase statistical power for the monitoring of genetic erosion in subsequent studies and reduce potential effects of ascertainment bias, we recommend to aim for a higher number of SNP markers (min. several hundred; e.g., Cammen et al, 2018 ; Ewart et al, 2019 ; Stronen et al, 2019a ), consider second‐generation sequencing of microsatellites (Curto et al, 2019 ), or data from WGS (Larsson et al, 2019 ; Loog et al, 2020 ; White et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to increase statistical power for the monitoring of genetic erosion in subsequent studies and reduce potential effects of ascertainment bias, we recommend to aim for a higher number of SNP markers (min. several hundred; e.g., Cammen et al, 2018 ; Ewart et al, 2019 ; Stronen et al, 2019a ), consider second‐generation sequencing of microsatellites (Curto et al, 2019 ), or data from WGS (Larsson et al, 2019 ; Loog et al, 2020 ; White et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the climate warming that occurred after the LGM in the Northern Hemisphere reduced effective population sizes, genetic diversity, and/ or census counts of other Arctic species like the polar bear Ursus maritimus (Miller et al . 2012) and the Arctic fox Vulpes lagopus (Larsson et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, population reconstructions showed that temperature increases reduced the effective population size of three penguin genera (Eudyptes, Pygoscelis, and Aptenodytes) in Antarctica (Cole et al 2019), highlighting ecosystem-wide responses to climate changes in the Antarctic ocean in the past. Similarly, the climate warming that occurred after the LGM in the Northern Hemisphere reduced effective population sizes, genetic diversity, and/ or census counts of other Arctic species like the polar bear Ursus maritimus (Miller et al 2012) and the Arctic fox Vulpes lagopus (Larsson et al 2019). Global warming has also been implicated as a major factor in the mass extinction of Late Quaternary megafauna in the Northern Hemisphere (Lorenzen et al 2011, Lord et al 2020, Stewart et al 2021; but see Sandom et al 2014).…”
Section: Past Population Trajectorymentioning
confidence: 99%
“…However, humans may not always be to blame. Studies on Musk ox and Kea interestingly identified environmental changes as the most important drivers of diversity loss suggesting prolonged histories of small population size (Campos et al 2010;Dussex et al 2015), while (Larsson et al 2019) revealed a complex interplay of climatic and anthropogenic factors in arctic fox. There is also contradicting evidence and hence an ongoing debate on the role of humans in the Late Quaternary megafauna mass extinction (Koch and Barnosky 2006;Campos et al 2010;Sandom et al 2014;Lord et al 2020;Stewart et al 2021).…”
Section: Introductionmentioning
confidence: 99%